Alcohol intake and endogenous sex hormones in women: Meta‐analysis of cohort studies and Mendelian randomization - Tin Tin, S; Smith‐Byrne, K; Ferrari, P; Rinaldi, S; McCullough, ML; Teras, LR; Manjer, J; Giles, G; Le Marchand, L; Haiman, CA; Wilkens, LR; Chen, Y; et al. (Wiley, 2024)
Background: The mechanisms underlying alcohol‐induced breast carcinogenesis are not fully understood but may involve hormonal changes. Methods: Cross‐sectional associations were investigated between self‐reported alcohol intake and serum or plasma concentrations of estradiol, estrone, progesterone (in premenopausal women only), testosterone, androstenedione, dehydroepiandrosterone sulfate, and sex hormone binding globulin (SHBG) in 45 431 premenopausal and 173 476 postmenopausal women. Multivariable linear regression was performed separately for UK Biobank, European Prospective Investigation into Cancer and Nutrition, and Endogenous Hormones and Breast Cancer Collaborative Group, and meta‐analyzed the results. For testosterone and SHBG, we also conducted Mendelian randomization and colocalization using the ADH1B (alcohol dehydrogenase 1B) variant (rs1229984). Results: Alcohol intake was positively, though weakly, associated with all hormones (except progesterone in premenopausal women), with increments in concentrations per 10 g/day increment in alcohol intake ranging from 1.7% for luteal estradiol to 6.6% for postmenopausal dehydroepiandrosterone sulfate. There was an inverse association of alcohol with SHBG in postmenopausal women but a small positive association in premenopausal women. Two‐sample randomization identified positive associations of alcohol intake with total testosterone (difference per 10 g/day increment: 4.1%; 95% CI, 0.6–7.6) and free testosterone (7.8%; 4.1–11.5), and an inverse association with SHBG (–8.1%; –11.3% to –4.9%). Colocalization suggested a shared causal locus at ADH1B between alcohol intake and higher free testosterone and lower SHBG (posterior probability for H4, 0.81 and 0.97, respectively). Conclusions: Alcohol intake was associated with small increases in sex hormone concentrations, including bioavailable fractions, which may contribute to its effect on breast cancer risk.